Temporalities in conlict: body and absence in the modern artistic practices in Argentina (2012)
The relations hips between the image and the memory have been one of the most relevant subjects, in the critical, theoretical and academic relection, in the last decade.This refers specially to those manifestations connected to the traumatic memory. Photography and cinema, among other artistic expressions, have faced the way in which the violence’s memory and its features are revealed not only through the places, objects and bodies of the victims but the later generations. In this way, both memory and post-memory coexist and nourish many modern artistic practices in Latin America. In this paper, we are going to study some works created by several Argentinean artistsand ilmmakers in which the corporality (the absence of ones’ bodies) plays an essential role. On one hand, we are going to talk about the violence victims’ (im-) possibility of representation, and on the other hand, we are going to talk about the resigniication of the temporality through this kind of works.